Bipolar Seesaw of Atmospheric CO2 Between North Pacific and Southern Ocean at Millennial Timescales - Yi Zhong; Yanguang Liu; Jimin Yu; Chijun Sun; Qin Wen; Sev Kender; Keiji Horikawa; Xu Zhang; Michael E. Weber; Siqi Li; Hu Yang; Stefanie Kaboth‐Bahr; et al. (Geophysical Research Letters)
Abstract The interhemispheric relation of deep‐water ventilation and surface‐ocean productivity may have played a prominent role in past atmospheric CO2 regulation. However, how these processes vary on orbital‐millennial timescales remains poorly understood. Here, we present high‐resolution proxy data and model simulations on the variability of biological productivity and deep water circulation for the abyssal northwestern Pacific Ocean spanning 20–60 kyr. We found that enhanced surface productivity increased during Heinrich Stadials (HS) and long term, caused by intensified westerly winds and associated dust fertilization, implying CO2 extraction from the atmosphere and increased nutrient supply to the euphotic zone. A similar increase in productivity for the Southern Ocean during Heinrich events implies enhanced upwelling and exhalation of CO2 to the atmosphere, indicative for an interhemispheric carbon cycle seesaw on millennial time scales. However, the longer‐term global cooling demonstrates that deep ocean carbon storage and degassing was predominantly modulated by the North Pacific Ocean.